Wide Range of Carbapenem-resistant Enterobacteriaceae Incidence and Trends in Emerging Infections Program Surveillance, 2012–2015. (4th October 2017) - Duffy, Nadezhda; Brown, Cedric J; Bulens, Sandra N; Bamberg, Wendy; Janelle, Sarah J; Jacob, Jesse T; Bower, Chris; Wilson, Lucy; Vaeth, Elisabeth; Lynfield, Ruth; Vagnone, Paula Snippes; Phipps, Erin C; et al.
Abstract: Background: Carbapenem-resistant Enterobacteriaceae (CRE) are an urgent threat in the United States because of high morbidity and mortality, few treatment options, and potential for rapid spread among patients. To assess for changes in CRE epidemiology and risk among populations, we analyzed CDC Emerging Infections Program (EIP) 2012–2015 surveillance data for CRE. Methods: Active, population-based CRE surveillance was initiated in January 2012 at 3 EIP sites (GA, MN, OR) and expanded to 5 additional sites (CO, MD, NM, New York, TN) by 2014. An incident case was the first Escherichia coli, Enterobacter, or Klebsiella isolate (non-susceptible to at least one carbapenem and resistant to all third-generation cephalosporins tested) collected from urine or a normally sterile body site from a patient during a 30-day period. Data were collected from patients' medical records. Cases were hospital-onset (HO) or long-term care facility (LTCF) onset if patients were in the respective facility ≥3 days prior to culture or at the time of culture; and community-onset (CO) otherwise. We calculated incidence rates based on census data for EIP sites and described by type of infection onset. Results: A total of 1, 582 incident CRE cases were reported in 2012–2015. Most cases (88%) were identified through urine cultures; 946 (60%) were female, and median age was 66 years (interquartile range: 55–77). The median incidence by site was 2.95 per 100, 000 population (range: 0.35–8.98). Among the three sites with four full years of data, a different trend was seen in each (Figure). Trends in GA and MN were statistically significant, and no significant trend was seen in OR. Overall, 480 cases (30%) were HO, 524 (33%) were LTCF onset, and 578 (37%) were CO. Of CO cases, 308 (53%) had been hospitalized, admitted to a long- term acute care hospital or were a LTCF resident in the prior year. Conclusion: CRE incidence varied more than 20-fold across surveillance sites, with evidence of continued increases in MN. Measuring impact of programs aimed at reducing CRE transmission in other regions will require obtaining local data to identify cases occurring during and after healthcare facility discharge. Further study of changes in incidence in some settings and areas might offer opportunities to refine and expand effective control strategies. Disclosures: All authors: No reported disclosures.